2004
DOI: 10.1038/sj.bjp.0706006
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP‐mediated inhibition of gallbladder contractility: role of K+ channel activation and Ca2+ signaling

Abstract: 1 We have examined the mechanisms of cAMP-induced gallbladder relaxation by recording isometric tension and membrane potential in the intact tissue, and global intracellular calcium concentrations ([Ca 2 þ ] i ) and F-actin content in isolated myocytes. 2 Both the phosphodiesterase (PDE) inhibitor, IBMX (100 mM) and the adenylate cyclase activator, forskolin (2 mM) caused decreases in basal tone that exhibited similar kinetics. IBMX and forskolin both caused concentration dependent, right-downward shifts in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…Recent reports have demonstrated that calcium facilitates fatty acid and protein-induced CCK secretion [21,22]. Furthermore, calcium also participates in the mechanism of action of CCK on gallbladder contraction [23][24][25] and pancreatic enzyme production [26][27][28]. Our data suggest that calcimimetics have no relevant role in the release of this hormone.…”
Section: Discussioncontrasting
confidence: 40%
“…Recent reports have demonstrated that calcium facilitates fatty acid and protein-induced CCK secretion [21,22]. Furthermore, calcium also participates in the mechanism of action of CCK on gallbladder contraction [23][24][25] and pancreatic enzyme production [26][27][28]. Our data suggest that calcimimetics have no relevant role in the release of this hormone.…”
Section: Discussioncontrasting
confidence: 40%
“…The excitability of GBSM cells is modulated by Ca 2ϩ influx via VDCCs (1, 50) and intracellular Ca 2ϩ mobilization (1,(27)(28)(29)38). We evaluated the role of VDCCs in Ca 2ϩ -wave activity to determine the association among Ca 2ϩ waves, Ca 2ϩ flashes, or APs.…”
Section: Discussionmentioning
confidence: 99%
“…In arterial smooth muscle cells, nanomolar concentration CCCP causes generation of ROS and activation of Ca 2ϩ -activated K ϩ channels (53). Ca 2ϩ -activated K ϩ channels are present in GBSM and are involved with reducing excitability through a hyperpolarization (28,34,54), which may explain the tendency for plasma membrane hyperpolarization observed in some GBSM immediately after the application of CCCP. It is also possible that CCCP and FCCP reduced APs and Ca 2ϩ flashes through transient activation of other types of potassium channels known to exist in GBSM (17,31,34,54).…”
Section: Discussionmentioning
confidence: 99%